Blood plasma essential aminoacids of stable and unstable stenocardia patients - Zavalskaya, T.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The study involved patients with stable and unstable stenocardia. The ion exchange liquid-column chromatography method was used. In unstable stenocardia patients compared with stable stenocardia patients, a significant increase in the contents of such aminoacids is revealed: arginine, valine, histidine, lysine, threonine, taurine.